Efficacy of atosiban for repeated embryo implantation failure: A systematic review and meta-analysis - Wang, Ruxin; Huang, Haixia; Tan, Yong; Xia, Guicheng (Frontiers in Endocrinology, 2023)
Background: Repeated embryo implantation failure (RIF) posed a significant challenge in assisted reproduction. Evidence of its therapeutic effectiveness including atosiban used around embryo transfer to improve pregnancy outcomes in RIF patients undergoing in vitro fertilization-embryo transfer (IVF-ET) remained inconsistent. This study aimed to explore the efficacy of atosiban on pregnancy outcomes of patients with RIF who received IVF-ET. Methods: The research was designed using the PICOS format. A systematic search of four English databases, PubMed, EMBASE, Web of Science, Cochrane Library, and one Chinse database, China National Knowledge Infrastructure (CNKI) was conducted. The time range was from inception to December 10, 2022. Then trials comparing the efficacy of atosiban and control group on pregnancy outcomes in RIF patients who receive IVF-ET were included. Subgroup analysis and sensitivity analysis were performed to reduce the influence of heterogeneity between included studies. Risk ratio (RR) and 95% confidence interval (CI) were calculated. The main outcome measure was clinical pregnancy rate (CPR). For the analyses, StataMP 17.0 (Stata Corporation, USA) was used. Results: Two prospective randomized controlled trials (RCTs), one prospective cohort study and four retrospective cohort studies were included. Our results showed that atosiban was associated with higher clinical pregnancy rate (RR=1.54, 95% CI: 1.365–1.735, P=0.000, I2=0.0%). The results of subgroup analysis based on study types (prospective randomized controlled clinical trial, retrospective cohort study and prospective cohort study) showed that in all types of studies, CPR of atosiban group was significantly higher than controlled group. The results of subgroup analysis based upon the diagnostic criteria of number of previous embryo transfer failures showed that the intervention of atosiban improved the CPR whether in participants with 2 previous ET failures or in participants with 3 previous ET failures. Nevertheless, the incidence of ectopic pregnancy, multiple pregnancy, and miscarriages were not significantly different between the case and control groups. Conclusion: For women who are undergoing IVF-ET and have experienced repeated embryo implantation failure, atosiban may be an important factor in enhancing pregnancy outcomes. To confirm this conclusion, more thorough, prospective randomized controlled studies of sizable sample sizes with well design are required.